2020
DOI: 10.1093/gerona/glaa317
|View full text |Cite
|
Sign up to set email alerts
|

Association of Paraspinal Muscle Measurements on Chest Computed Tomography With Clinical Outcomes in Patients With Severe Coronavirus Disease 2019

Abstract: Background Skeletal muscle depletion is common in the elderly and individuals with chronic comorbidities, who have an increased risk of developing severe coronavirus disease 2019 (COVID-19), which is defined by hypoxia requiring supplemental oxygen. This study aimed to determine the association between skeletal muscle depletion and clinical outcomes in patients with severe COVID-19. Methods One hundred and sixteen patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…The median age was 74 (68-79) years, and the median BMI was 22.4 kg/m 2 (20.5-24.5). Among the participants, 93.8% (122) had at least one comorbidity, and the most common comorbidities were type 2 diabetes mellitus, hypertension, and chronic obstructive pulmonary disease, with a prevalence of 23.8% (31), 26% (20), and 16.9% (22), respectively. The median time from the onset of symptoms at admission was 6 days (4-8), median body temperature was 37.4°C (36.8-38.6), and median oxygen saturation on room air was 88% (86-89).…”
Section: Resultsmentioning
confidence: 99%
“…The median age was 74 (68-79) years, and the median BMI was 22.4 kg/m 2 (20.5-24.5). Among the participants, 93.8% (122) had at least one comorbidity, and the most common comorbidities were type 2 diabetes mellitus, hypertension, and chronic obstructive pulmonary disease, with a prevalence of 23.8% (31), 26% (20), and 16.9% (22), respectively. The median time from the onset of symptoms at admission was 6 days (4-8), median body temperature was 37.4°C (36.8-38.6), and median oxygen saturation on room air was 88% (86-89).…”
Section: Resultsmentioning
confidence: 99%
“…8,[25][26][27][28] Skeletal muscle, particularly intramuscular fat, which is the main active substance, can participate in immune response by releasing cytokines. 13,29 A study revealed that IL-15 levels in serum are inversely proportional to age and exert immune function by promoting muscle cell development and reducing fat infiltration, which can partially explain why reduced skeletal muscle mass causes immune dysfunction. 30,31 In other words, skeletal muscle mass reduction is associated with increased intramuscular fat, which is more likely to release numerous cytokines, leading to systemic inflammation, thereby aggravating the disease.…”
Section: Discussionmentioning
confidence: 99%
“…By limiting unit thresholds of À29 to +150, skeletal muscles were distinguished from surrounding tissues, implying that skeletal muscles could be selected in the designated area. 13,19,20 PMA was defined as any muscle behind the spine and the 12th rib, and paraspinal muscle radiodensity (PMD) was the average density of the area, as depicted in Fig. 2.…”
Section: Paraspinal Muscle Measurementmentioning
confidence: 99%
See 2 more Smart Citations